620 Description of 14&6 variant on polysomnography. (3rd May 2021) - Powell, Weston; Nash, Jessica; Ruth, Chris; Chan, Jeremy; Lockhart, Carey
Abstract: Introduction: Benign variants or incidental findings are often identified on routine polysomnography. One such variant is 14-and-6 hertz positive spikes, first described on EEG in 1951; however, the significance of 14-and-6 positive spikes found on polysomnography has not been previously described. Methods: We conducted a retrospective review of patients with 14-and-6 Hz spikes on polysomnography and compared clinical findings on polysomnography with age and sex-matched controls. Results: Mean age was 8.6 years (range 2–16). Sleep indices did not differ between cases and controls. Patients with 14-and-6 Hz spikes had lower obstructive apnea-hypopnea index and were less likely to be diagnosed with obstructive sleep apnea. Patients with 14-and-6 Hz spikes did not differ from controls in frequency of formal neurology evaluation, whether a full EEG was obtained, or neurologic diagnoses. Patients with 14-and-6 Hz spikes were less likely to be diagnosed with behavioral or developmental disorders. Conclusion: 14-and-6 Hz spikes can be seen in children of all ages and does not seem to be associated with any sleep, neurologic, or developmental disorders. Support (if any):